2021
DOI: 10.3390/cancers13194816
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Landscape of Angiosarcoma: A Targeted and Immunotherapy Biomarker Analysis

Abstract: We performed a retrospective analysis of angiosarcoma (AS) genomic biomarkers and their associations with the site of origin in a cohort of 143 cases. Primary sites were head and neck (31%), breast (22%), extremity (11%), viscera (20%), skin at other locations (8%), and unknown (9%). All cases had Next Generation Sequencing (NGS) data with a 592 gene panel, and 53 cases had Whole Exome Sequencing (WES) data, which we used to study the microenvironment phenotype. The immunotherapy (IO) response biomarkers Tumor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 52 publications
4
27
0
Order By: Relevance
“…This analysis is constrained by a limited number of samples for analysis; yet, we identified the same number of immune clusters (four) as the recent report by Espejo-Freire et al . 55 Cancer-associated fibroblasts, a stromal population not included in the Petitprez et al sarcoma immune classification, 47 are upregulated in a subset of angiosarcomas. 55 We identified a trend toward inferior PFS in these patients, potentially indicating a mechanism of resistance to ICB, a finding confirmed in select carcinomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This analysis is constrained by a limited number of samples for analysis; yet, we identified the same number of immune clusters (four) as the recent report by Espejo-Freire et al . 55 Cancer-associated fibroblasts, a stromal population not included in the Petitprez et al sarcoma immune classification, 47 are upregulated in a subset of angiosarcomas. 55 We identified a trend toward inferior PFS in these patients, potentially indicating a mechanism of resistance to ICB, a finding confirmed in select carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“… 55 Cancer-associated fibroblasts, a stromal population not included in the Petitprez et al sarcoma immune classification, 47 are upregulated in a subset of angiosarcomas. 55 We identified a trend toward inferior PFS in these patients, potentially indicating a mechanism of resistance to ICB, a finding confirmed in select carcinomas. 56 Additionally, gene set enrichment analysis found that upregulated KRAS signaling, a pathway that we found to be significantly altered in CHN angiosarcoma, was associated with PFS ≥16 weeks after ICB.…”
Section: Discussionmentioning
confidence: 99%
“…HSA occurs in ~50,000 canines per year in the United States ( 16 ), and its frequency is higher than that in humans, rendering this a useful model for the study of human intractable disease that requires early detection and effective therapeutic strategy. Developments in genome-wide approaches have enabled the comprehensive analysis of disease-related gene mutations in humans and animals ( 17 , 18 ). Mutated canine genes related to HSA have been searched using exome sequencing, and the 1047th histidine residue (H1047) of p110α phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit alpha (PIK3CA) was found to be highly mutated ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Angiosarcoma is a high-grade malignant soft tissue tumor, originating from lymphatic or vascular endothelial cells, which exhibit rapid proliferation and invasion capacity that is associated with a poor prognosis [ 1 , 2 ]. Angiosarcoma may arise in any location of the body, such as bone, liver, heart or breast; it occurs most frequently in the skin and soft tissues [3] .…”
Section: Introductionmentioning
confidence: 99%